Uji Efek Analgesik Ekstrak Etanol Mencit Jantan dengan Metode Tail-Flick - Widiarti, Widiarti; Andrajati, Retnosari; Amin, Juheini (UI Scholars Hub, 2012)
In the previous study the analgesic effect of Cinnamommum zeylanicum Breyn had been investigating. The aim of this study was to investigate analgesic effect of the 70% ethanol extract of cinnamon bark (Cinnamommum zeylanicum Breyn.). This study used Tail Flick method at 25 male mice which have passed sensitivity test, divided into five groupes. Group I as negative control was administered 0,5% CMC, group Il as positive control was administered tramadol HCI, group Ill, IV and V was administered extract of cinnamon bark at 8; 16 and 32 mg/20 g BW. Drugs were orally administered to mice. The reaction of time exhibited by each animal was counted for two hour with interval thirty minutes. The Result revealed that the prepared extract in at the all dose, had analgesic effect significantly in all groups which have been studied (p< 0,05) in comparison to the negative control, to the highest analgesic effect by dose (32 mg/ 20 g BW). Our results showed that the analgesic effect of extract (32 mg/20 g BW) the same with tramadol hidroclorida.